2003
DOI: 10.1016/s0967-0661(02)00231-9
|View full text |Cite
|
Sign up to set email alerts
|

Iterative controller optimization for nonlinear systems

Abstract: Recently, a data-driven model-free control design method has been proposed in (7; 6) for linear systems. It is based on the minimization of a control criterion with respect to the controller parameters using an iterative gradient technique. In this paper, we extend this method to the case where both the plant and the controller can be nonlinear. It is shown that an estimate of the gradient of the control criterion can be constructed using only signal-based information obtained from closed loop experiments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 6 publications
(1 reference statement)
0
28
0
Order By: Relevance
“…Hjalmarsson (1998) and Sjöberg and De Bruyne (1999). See also Sjöberg et al (2003) for an algorithm tailored especially for non-linear systems.…”
Section: Iterative Feedback Tuningmentioning
confidence: 99%
“…Hjalmarsson (1998) and Sjöberg and De Bruyne (1999). See also Sjöberg et al (2003) for an algorithm tailored especially for non-linear systems.…”
Section: Iterative Feedback Tuningmentioning
confidence: 99%
“…Secondly it is not restricted by the type of process. Even though the theory is developed for linear systems, the references [11,35] states that …”
Section: Characteristics Of Iterative Feedback Tuningmentioning
confidence: 99%
“…The Iterative Feedback Tuning method does generate the true first order approximation of the gradients for a nonlinear process. The bias can be expected to be small for many practical applications [35] and successful tuning of PID loops for industrial processes has been reported in [23,16]. The theory has furthermore been extended to cover optimization of multivariable processes, which implies that more experiments in each iteration are necessary [14,12,19] and to cover non-minimum phase and time delay systems [22].…”
Section: Fig 2 Schematic Representation Of the Iterative Feedback Tmentioning
confidence: 99%
“…Two strategies were adopted in order to deal with this heavy friction: The one was to separate the tuning of the feedback and feed forward controllers and the other was to employ the Broyden-Fletcher-Glodfard-Shanno (BFGS) method as a quasi-Newton method in a parameter update law. (3) In [7] the data-driven model free control design method that was introduced by Hjalmarsson in 1994 was extended to a case where both the plant and the controller are allowed to be nonlinear. In this paper it was shown that one can obtain an estimate of the model of the plant experimentally by using the closed loop measured data (input and output signals).…”
Section: Ift and Muc Applicationsmentioning
confidence: 99%